Asymmetric synthesis of (-)-alpha-conhydrine - Kandula, Subba Rao V.; Kumar, Pradeep (Tetrahedron-Asymmetry, 2005)
The enantioselective synthesis of (-)-alpha-conhydrine has been achieved by two different synthetic routes. The key steps include Sharpless asymmetric dihydroxylation, regioselective opening of a cyclic sulfate and Wittig olefination. (c) 2005 Elsevier Ltd. All rights reserved.